Brownification in the Eastern Mediterranean Sea: effect of simulated terrestrial input on the planktonic microbial food web in an oligotrophic sea - Ktistaki, Georgia; Magiopoulos, Iordanis; Corno, Gianluca; Courboulès, Justine; Eckert, Ester M.; González, Jose; Kalantzi, Ioanna; Middelboe, Mathias; Symiakaki, Katerina; Tsapakis, Manolis; Vidussi, Francesca; Pitta, Paraskevi (Frontiers in Marine Science, 2024)
Terrestrial input to marine and freshwater ecosystems colors the water yellow-brown, causing a phenomenon called "brownification". The effect of brownification on the marine pelagic microbial food web was studied in the oligotrophic eEastern Mediterranean in June 2021 by adding HuminFeed in a 15-day mesocosm experiment with 2 treatments: Control (C, no addition) and HuminFeed (HF, single dose of HuminFeed, 2 mg L -1 ); and 3 replicates per treatment. HuminFeed caused shading, leading to a decrease in the abundance of photo-autotrophic organisms (cyanobacteria Synechococcus and diatoms). Bacteria were positively affected by the HF addition (mainly in terms of production rather than abundance), benefiting either directly from the dissolved organic carbon (DOC) contained in HuminFeed or indirectly from the trophic cascade through the food web. Despite the decrease in HF bacterial abundance during the experiment, an increase in both the high 2 nucleic acid containing bacteria% and heterotrophic bacterial production were observed, suggesting higher activity at the single cell level. In the HF treatment, the increased abundance of dinoflagellates observed could be due to either a dominance of mixotrophic species or a released from predation by copepods. Both ciliates and copepods were severely impacted by HuminFeed, showing lower abundance and distorted forms (ciliates) and reduced reproductive potential (copepods). In conclusion, in the ultraoligotrophic eEastern Mediterranean, the simulated brownification negatively affected autotrophs and top predators while benefiting bacteria, thus indicating a shift in the structure of the plankton food web.